Genetic analysis of Certain Clones, Hybrids and Inbreds in Cocoa - Rose Mary Francies (Department of Plant Breeding and Genetics, College of Horticulture, 1998)
Genetic studies in cocoa (Theobroma cacao L.) using various population viz., clones, biclonal crosses, biclonal pair crosses and inbreds were undertaken in College of Horticulture, Kerala Agricultural University, Thrissur, during 1994-97. The study assessed variability, association of yield attributes and relative importance of these attributes for yield variation using multiple regression and path analysis. Selection indices, inbreeding depression and limits to genetic diversity for heterosis were also worked out. Wide spectrum of variability existed in the populations studied. The highest variability was observed in yield of dry beans/tree and precocity of bearing (pods/tree - 5 years from planting), whereas, traits pod width and bean width showed low variability. Clones GI 10.2, S 27.16, GI 14.17 of Clonal base population, hybrids H'8 (GI 5.9 x GII 23.3), H2 (M 13.12 x GI 5.9) of Series IV biclonal crosses and hybrids H4 (M 16.9 x GII 19:5), H3 (M 16.9 x GII 20.4) of Series 11 biclonal crosses, exhibited superior yield - performance. Yield however, recorded only moderate heritability and therefore moderate expected genetic advance. Strong correlation was observed for yield with pod weight, dry weight/bean and efficiency index but not with precocity of bearing, chlorophyll contents and net photosynthesis rate. Multiple regression and path analysis revealed the importance of dry weight/bean, bean size and